Transnational torture : law, violence, and state power in the United States and India - Lokaneeta, Jinee (New York : New York University Press, 2016)
This text focuses on the legal and political discourses on torture in India and the United States - two common-law based constitutional democracies - to theorize the relationship between law, violence, and state power in liberal democracies.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 1, 2016).
Keywords: Torture -- United States; Torture -- India; Law; India; United States of America, USA; Comparative law; Criminal law: offences against the person